Validitas Lembar Kerja Siswa pada Pembelajaran Pecahan dengan Pendekatan Matematika Realistik Berbantuan Manuskrip Faraidh - Sera Delta Tanjung; Anizar Ahmad; Cut Morina Zubainur (Universitas Syiah Kuala, 2019)
Realistic approach is a learning approach that examines topics / concepts of mathematics through contextual problems. The goal is to create a memorable and meaningful learning through experience. This mathematical experience gained from the experience of mathematics. The experience can be obtained from the culture. Etnomatematika is a form of mathematics were influenced or based on the culture that exists in the community, either in the form of religion, artifacts and customs. One etnomatematika that develops in the people of Aceh and close to the students is about science faraidh (the division of the estate). Faraidh etnomatematika utilization of science is in accordance with the purpose of education in Aceh that are nuanced Islamic education as an area that bersyariat Islam. However, etnomatematika-based learning tools that are not available, so it needs to be an effort to help teachers to develop devices based learning etnomatematika. This study aims to determine the process and outcome-based learning software development etnomatematika valid, practical, and effective. The development method used for unmet valid, practical and effective is the method Plomp, which includes the initial assessment phase, the design / prototyping, and assessment. The subjects were a group of junior high school students in grade VIID Al-Fityan IT as a subject limited test and one class graders from junior IT VIIB Al-Fityan Aceh Besar as subjects to test the practicalities and effectiveness of the learning. The results of this study obtained etnomatematika based learning tools that meet the criteria for a valid, practical, and effective.